Olive Tourism motivations, activities and experiences: Perspectives from a Portuguese Delphi Panel - Francisco Dias; Fernanda Oliveira (Via@)
The olive heritage is a central element of many of the Mediterranean rural territories and is the basis for the development of a range of infrastructures, activities and experiences that make up olive tourism. The trend towards healthier, more genuine and authentic consumption has contributed to a growing demand that increasingly enhances values and resources that represent the rural world, including those relating to olive growing. Through the Delphi method and the collaboration of a panel of 12 Portuguese experts in olive tourism, this study aims to identify the most important range of activities, experiences and motivations in the context of olive tourism. It is intended to contribute to a more accurate knowledge of the subject, particularly the aspects that allow the development of an offer more aligned with the current motivational trends of tourist demand.The results show that the activities and experiences considered most important in the context of olive tourism are those directly related to olive oil tasting and typical gastronomic dishes where olive oil is the most remarkable element. Additionally, it emerges that gastronomic tourism is the tourism product that presents the greatest affinity and complementarity with olive tourism.